Latest Permian Peltasperm Plant From Southwest China and Its Paleoenvironmental Implications - Feng, Zhuo; Wei, Hai‐Bo; Ye, Rong‐Hui; Sui, Qun; Gou, Xu‐Dong; Guo, Yun; Liu, Lu‐Jun; Yang, Shi‐Ling (Frontiers in Earth Science, 2020)
A monospecific flora containing a peltasperm species, Germaropteris martinsii, is discovered from the uppermost Permian Kayitou Formation of Southwest China. The epidermal characteristics of G. martinsii from the South China Block are described for the first time on the basis of charcoalified specimens. The plant is characterised by small, leathery foliage with prominent papillate epidermal cells and slightly sunken stomata. The stomatal apertures are covered by the long papillae of the surrounding subsidiary cells. The specific epidermal traits suggest that G. martinsii is a highly environmentally tolerant taxon that probably formed monospecific communities during the dramatic degradation of the peat-forming rainforest ecosystems. The frequent appearance of charcoalified leaves in the flora demonstrates that intense wildfires were prevalent at the time. The appearance and reflectance value (1.33%) of these charcoalified leaves reveal that they were formed at temperatures of 450–500°C during brief surface fires. Our study indicates that the terrestrial ecosystems may have been frequently subjected to desiccation and was vulnerable to the spread of fires as a result of the end-Permian biotic crisis in the tropics of the eastern Tethys region.